2012
DOI: 10.1371/journal.pone.0045333
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in South Asians: An In-Depth Qualitative Study to Explore Motivations and Facilitators

Abstract: BackgroundPeople of South Asian backgrounds living in the UK have a five-fold increased risk of diabetes and a two-fold increased risk of heart disease when compared to the general population. Physical activity can reduce the risk of premature death from a range of conditions. The aim of the study was to explore the motivating and facilitating factors likely to increase physical activity for South Asian adults and their families, in order to develop successful interventions and services.Methodology/Principal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
131
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(147 citation statements)
references
References 32 publications
14
131
1
1
Order By: Relevance
“…Dancing is one activity that women repeatedly mentioned as enjoyable and that they would dance in groups at cultural centres or individually in homes by putting on music (Eyler et al, 1998). Jepson et al (2012) found South Asian women in all focus groups mentioned activities such as exercise classes, going to the gym, and being a part of team sports such as netball as current activities they were participating it. Two activities that were often brought up that the women engaged in or would like to were swimming and walking.…”
Section: Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Dancing is one activity that women repeatedly mentioned as enjoyable and that they would dance in groups at cultural centres or individually in homes by putting on music (Eyler et al, 1998). Jepson et al (2012) found South Asian women in all focus groups mentioned activities such as exercise classes, going to the gym, and being a part of team sports such as netball as current activities they were participating it. Two activities that were often brought up that the women engaged in or would like to were swimming and walking.…”
Section: Physical Activitymentioning
confidence: 99%
“…Studies conducted in the UK by Jepson et al (2012) and Sriskantharajah and Kai (2007) found these women express similar benefits of PA including social support (Jepson et al, 2012;Sriskantharajah & Kai, 2007), weight loss (Jepson et al, 2012;Sriskantharajah & Kai, 2007) and increased self-esteem (Jepson et al, 2012). The women in Jepson et al (2012) study mentioned social opportunities that PA provided as the most important benefit whereas women in Sriskantharajah and Kai (2007) said maintenance of their weight was most important because they felt body image and physical appearance was constantly spoken about in society. The main benefit for South Asian women over 60 years of age was increased mobility and independence (Sriskantharajah & Kai, 2007).…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…South Asian populations and Indian, Pakistani and Bangladeshi women and children in particular are significantly less likely to meet the UK PA guidelines than the White British group (2,5). Barriers, enablers and facilitators to PA for BME groups have been explored, especially in relation to South Asian populations (6,7). Research suggests BME groups face generally similar barriers to the UK population as a whole with limitations such as childcare, motivation and lack of time predominating (7).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers, enablers and facilitators to PA for BME groups have been explored, especially in relation to South Asian populations (6,7). Research suggests BME groups face generally similar barriers to the UK population as a whole with limitations such as childcare, motivation and lack of time predominating (7). Additional, and potentially more subtle, barriers relate to differences in perceptions about the benefits of PA, what counts as PA, community expectations about participation, and deeper socio-cultural processes of exclusion and discrimination (8).…”
Section: Introductionmentioning
confidence: 99%